Buddhism Has Always Been Posthuman:Philosophical Contributions to the Transhumanist Project - Tormen, Francesco (Canadian Journal of Buddhist Studies, 2023)
This article draws a comparison between Buddhism (especially Mahāyāna) and two contemporary philosophies: posthumanism and transhumanism. Regarding the former, I argue the compatibility between Buddhism and posthumanism, especially regarding anti-essentialism and antianthropocentrism. Regarding the latter, I demonstrate Buddhism's openness to human enhancement and identify utilitarianism as an ethical common ground between Buddhism and transhumanism. I argue that Buddhist insights into the root causes of suffering could steer transhumanism toward a form of deep (or cognitive) utilitarianism. The Buddhist legacy could also contribute to the transhumanist project through its insights into the nature of consciousness, which could prove useful to philosophical analysis and neurophenomenological research.,